Systematic Literature Review: Efektivitas Model Flipped Classroom Dalam Pembelajaran Sekolah Dasar - Jaharah, Nisa; Gunawan, Indra; Yanti, Yuli; Maharani, Aulia (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to examine the effectiveness of the Flipped Classroom model in elementary education through a Systematic Literature Review (SLR) approach. The study is motivated by the need for innovative learning models that can enhance students’ motivation, engagement, and academic achievement in the context of 21st-century education. Data were collected from 86 Scopus-indexed articles published between 2020 and 2024 using the Publish or Perish software, and subsequently screened following the PRISMA guidelines. A total of 35 articles that met the inclusion criteria were analyzed using a bibliometric approach with the aid of VOSviewer software. The results reveal that the Flipped Classroom model has a positive impact on improving students’ learning motivation, engagement, and conceptual understanding at the elementary school level. The publication trend showed a significant increase in 2021, mainly influenced by the widespread adoption of distance learning during the COVID-19 pandemic. Indonesia, Malaysia, and Turkey emerged as the top three contributing countries in this research area. However, several challenges remain, including limited technological infrastructure, teachers’ readiness in designing digital learning, and the need for parental support at home. Overall, this study confirms that the Flipped Classroom is an effective instructional strategy to foster 21st-century skills in elementary education. The findings are expected to serve as a valuable reference for teachers, schools, and policymakers in developing innovative learning strategies that align with technological advancements and the characteristics of elementary school learners.